Pathogen Profile and Antimicrobial Susceptibility Patterns in Patients with Peritonitis: A Prospective Hospital-Based Study in Northern Tanzania (Tanzania Medical Journal, 2025)
BackgroundPeritonitis is a life-threatening surgical emergency and a major cause of morbidity and mortality worldwide. Appropriate antibiotic therapy is critical, yet misuse of antimicrobial agents contributes to the rise of resistant strains, especially in developing countries. Resistance leads to treatment failure and imposes financial burdens on both patients and healthcare systems. This study aimed to assess intra-abdominal pathogens and their antimicrobial susceptibility patterns among patients with peritonitis.MethodsThis was a hospital-based descriptive cross-sectional study conducted at Kilimanjaro Christian Medical Centre, northern Tanzania, between October 2019 and April 2020. All patients with peritonitis admitted to the surgical department were enrolled. Intraoperative peritoneal swabs were collected and cultured. Antimicrobial susceptibility testing was performed using the Kirby-Bauer method on Müller-Hinton agar and interpreted according to Clinical and Laboratory Standards Institute guidelines. Data were summarized using descriptive statistics and supplemented with information from patients’ clinical notes.ResultsA total of 39 patients were identified, of whom Thirty-five patients met eligibility criteria. The median age was 32 years (IQR: 20–48), and 51.4% were male. The most common isolates were Escherichia coli (42.4%) and Klebsiella pneumoniae (21.2%). Both were highly susceptible to amikacin and meropenem (100%), but showed low susceptibility to ceftriaxone (22% and 20%, respectively).Conclusion and recommendationsHigh levels of resistance to commonly used empirical antibiotics were observed, highlighting the need to revise empirical therapy for peritonitis in this setting. Rational use of antibiotics, alongside close monitoring of treatment responses, is essential to reduce morbidity, mortality, and the spread of antimicrobial resistance.